Epidural labor analgesia: a comparison of mixture of ropivacaine 0.125% with fentanyl versus ropivacaine 0.2% with fentanyl - Patel, Dipali L.; Sojitra, Bhavna H.; Rathod, Jigishaben D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Ropivacaine is more selective for sensory fibers when compared to other local anesthetics, producing less motor block. This permits better maternal ambulation and also allows for normal progression of labor, which translates into lesser instrumental deliveries and higher vaginal deliveries. Objective was to evaluate 0.125% versus 0.2% ropivacaine, with 2 μg/ml of fentanyl in epidural labor analgesia, regarding their sensory and motor block characteristics. Methods: This prospective study was conducted among 40 patients, 20 in each group [group A (0.125% ropivacaine with 2 µg/ml fentanyl), group B (0.2% ropivacaine with 2 µg/ml fentanyl)], for epidural labor analgesia in obstetrics and gynecology department (labor room). The efficacy of the drugs was tested by comparing the onset of analgesia, duration of labor analgesia, dose requirement, pulse, BP, sensory effect, motor effect, FHR, APGAR score and side effects. Results: Total duration of labor analgesia was 230.25 minutes with 55.68 SD and 186.25 minutes with 57.7 SD in group A and group B respectively (p<0.05). The total dose of ropivacaine used was 81.00 mg and 68.50 mg in group A and B respectively (p<0.05). Total dose of fentanyl required was 94.50 µg and 73.50 µg in group A and group B respectively (p<0.05). There was no significant difference found in hemodynamic parameters in both groups. Conclusions: Both the concentrations are effective in producing epidural labor analgesia. However, onset of analgesia was significantly faster with 0.2% ropivacaine. The required dose of ropivacaine was significantly higher in 0.125% ropivacaine. 0.2% ropivacaine shorten the duration of labor compared to 0.125% ropivacaine.